Optimasi Multiple Travelling Salesman Problem (M-TSP) pada Penentuan Rute Angkutan Sekolah menggunakan Algoritme Particle Swarm Optimization (PSO) - Muhammad Hidayat; Imam Cholissodin; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Daarussalaam Muslim Development Foundation (YPM) is an educational foundation located on Jl. Jendral Sudirman No 1, Swarga Bara, Sangatta Utara, East Kutai Regency, East Kalimantan. In YPM Daarussalam there are several schools, namely integrated Islamic kindergartens (TKIT), integrated Islamic elementary schools (SDIT), and integrated Islamic junior high schools (SMPIT). To help the departure and return of kindergarten and elementary school students, the foundation provides school transportation services that can be used for students in need. At present the number of students using school transportation services is 160 students out of a total of 832 students. Based on this number the foundation provides 8 cars with a capacity of 20 students per cars. This study aims to determine the optimal route for the Multiple Traveling Salesman Problem (M-TSP) problem using Particle Swarm Optimization (PSO) algorithm. In this study the school route is represented as particles which are divided into 3 segments, namely departure (segment 1), return 1 for grade 1,2 students, and kindergarten and (segment 2) and return 2 for grade 3-6 students which then the particles will be update the speed of each iteration to find the route with the best fitness value. The parameters used are the number of iterations = 538, particle size = 80, C1 = 1, and C2 = 1.5. The average fitness obtained is 2,297 with the best fitness value of 2,393, and with these results the foundation can cut the distance by 210,884 Km.